Pemberdayaan Perempuan pada Usaha Pengolahan Tape (Studi Kasus di Kabupaten Bondowoso) - -, Samsi (Universitas Brawijaya, Indonesia, 2009)
This research lift four main problem, that is 1) How profile of gender at business activity Processing of Tape in Sub-Province of Bondowoso East Java 2) How accessing and woman control and men to resource exist in business activity Processing of Tape 3) How resource impact and benefit to sides in concerned in effort Processing of Tape, and 4) How profile enableness of woman in grow economy society in Sub-Province of Bondowoso. In this research, its population is all housewife woman conducting processing of Tape in Sub-Province of Bondowoso East Java. Technique analysis data used to answer first target, and third is Technique Analysis Harvard or of Gender Framework Analysis ( GPA). Role of woman very dominant in all activity produce Tape, good in processing and also its marketing. Role of rather uppermost husband is at seeking of raw material produce Tape. Profile Activity reproduce related to food, child and clothes still predominated by daughter and wife while related to health and house many role of husband. Consistent with activity profile and access hence benefit of resource in this case earnings from effort processing of Tape is also predominated by woman.Keywords: empowerment, woman, small business